2019
DOI: 10.4314/gmj.v53i2.4
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the routes to inpatient care at the Pantang Hospital in Ghana via the criminal justice system

Abstract: Summary Objectives To develop knowledge of routes by which patients are admitted to Pantang hospital via the courts or police and to explore the factors that prevent discharge, rehabilitation or transfer to prison of these patients. Setting Pantang Psychiatric Hospital, Accra, Ghana, West Africa Design A cross-sectional exploratory qualitative study. Participants Adult patients with a psychiatric diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…This stated that the pressure on forensic psychiatry beds was so severe that transfers from prison are all but impossible and concluded that due to bed pressure, a review of transfer times was ‘currently unlikely to be feasible’ (Skipworth et al., 2019). Another study of the Patang hospital admissions in Ghana (Bone & Roberts, 2019) quantitatively reviewed 13 patients who met their inclusion criteria, exploring admission processes. Two prison transfers were reported with one waiting on remand for 4 years before transfer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This stated that the pressure on forensic psychiatry beds was so severe that transfers from prison are all but impossible and concluded that due to bed pressure, a review of transfer times was ‘currently unlikely to be feasible’ (Skipworth et al., 2019). Another study of the Patang hospital admissions in Ghana (Bone & Roberts, 2019) quantitatively reviewed 13 patients who met their inclusion criteria, exploring admission processes. Two prison transfers were reported with one waiting on remand for 4 years before transfer.…”
Section: Resultsmentioning
confidence: 99%
“…Another study of the Patang hospital admissions in Ghana (Bone & Roberts, 2019) quantitatively reviewed 13 patients who met their inclusion criteria, exploring admission processes. Two prison transfers were reported with one waiting on remand for 4 years before transfer.…”
Section: Studies From Outside the Ukmentioning
confidence: 99%
See 1 more Smart Citation
“…There are high rates of self-harm (46) and suicide (47,48), which though linked to ADHD in general population (49), are strongly associated with personality disorders, depression, substance misuse, and psychosis (50)(51)(52)(53)(54)(55)(56), and of violence (57-59), which is especially associated with ASPD (56,(60)(61)(62)(63)(64)(65). Despite this, prison mental health services remain chronically underresourced (66), with substantial delays in transfer to hospital for treatment in most countries where data is reported (67)(68)(69)(70), and limited access to and study of psychosocial and follow-up interventions that may be effective (27).…”
Section: Disproportionate Use Of Resourcesmentioning
confidence: 99%